The 2D Spectral Intrinsic Decomposition Method Applied to Image Analysis. (20th December 2017) - Sidibe, Samba; Niang, Oumar; Thioune, Abdoulaye; Abdou, Abdoul-Dalibou; Ngom, Ndeye Fatou
Abstract : We propose a new method for autoadaptive image decomposition and recomposition based on the two-dimensional version of the Spectral Intrinsic Decomposition (SID). We introduce a faster diffusivity function for the computation of the mean envelope operator which provides the components of the SID algorithm for any signal. The 2D version of SID algorithm is implemented and applied to some very known images test. We extracted relevant components and obtained promising results in images analysis applications.